Corporate governance and leverage on firm value: Evidence of Indonesian large firms - Perdana Wahyu Santosa; Any Setianingrum; Chadra Yusuf (University of Merdeka Malang, 2022)
This paper aims at the nexus of corporate governance, leverage, and firm value of selected Indonesian large firms in the 2014-2019 period. Specifically, the study is concerned about the effect of independent commissioner board size, institutional ownership, and audit committee size as proxies of corporate governance on firm value. The controlling variables are leverage and firm age. Panel regression analyzed secondary data collected from the LQ-45 index at Indonesia Stock Exchange firms as the large firms. The findings show that institutional ownership positively impacted firm value. However, the independent commissioner and audit committee exerted insignificant influence. The study results further showed that firm age and leverage significantly negatively impact firm value, respectively. Decisively, findings from this paper reflect that corporate governance positively influences firm value significantly. The study recommended that corporate governance dynamics in firms be empowered and re-examined, especially the audit committee's effectiveness. Both firm age and leverage do not affect productivity and firm value. The audit committee's role is more than optimal in carrying out the supervisory and control functions of the corporate management so that the responsibility of the management is considered transparent and results in an increase in shareholder trust. It is also recommended that the increase in firm age and excessive leverage be balanced with the creation of innovation and productivity of large firms.